Changing the Organization for Cataloguing in the BnF: a Long-term Project - Raccah, Philippe (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2002)
An inter-departmental committee of the French National Library has been working since the beginning of the year to review the overall cataloguing processes and the specific roles of the different sections within the library. It is recognized that there are mainly two different cataloguing processes within the library, which are distinct but equally important: legal deposit materials are to be catalogued with the best possible quality and as exhaustively as possible while other materials are acquired selectively and have to meet user needs within the library first. The catalogue of the library has to be as consistent as possible taking into consideration the staff and budget resources of the library.